Mekanisme Penjualan Kembali Sukuk Ijarah Perspektif Hukum Ekonomi Syariah - Yulianti , Yeni; Nazila Ramadhani , Rahma; Arzaki Zulmuayat, Muhammad; Elly, Yuni; Freddy, Rivaldo; Jaenuddin, Jaenuddin; Attaubah , Agi; Yulianti, Yeni; Ramadhani, Rahma Nazila; Jaenudin, Jaenudin; Hidayat, Agi Attaubah (ASAS, 2025)
Sukuk ijarah is one of the rapidly growing Islamic capital market instruments and is tradable in the secondary market. However, ambiguity remains regarding the resale mechanism of such sukuk, particularly concerning compliance with Sharia principles and prevailing legal frameworks. This study aims to examine the permissibility of sukuk ijarah resale from the perspective of Islamic economic law and to assess the role of Islamic financial institutions in ensuring Sharia-compliant transactions. The research employs a normative juridical method with data collected through literature study of primary and secondary legal sources. The findings indicate that the resale of sukuk ijarah is permissible as long as it is based on real assets rather than debt instruments and conducted at a fair market value. Key Sharia principles such as justice, transparency, and the prohibition of gharar, maysir, and riba are generally upheld in practice. Nonetheless, more comprehensive regulations are required to clarify the responsibilities of Islamic financial institutions in overseeing secondary market sukuk transactions. This study recommends regulatory enhancement to ensure a fair, transparent, and legally certain secondary market environment, thereby increasing investor confidence in Islamic financial instruments.